Workplace Violence Toward Hospital Staff and Volunteers: A Survey of an Italian Sample. Issue 1 (2nd January 2018) - Acquadro Maran, Daniela; Varetto, Antonella; Zedda, Massimo; Magnavita, Nicola
ABSTRACT: Interest in the phenomenon of workplace violence has increased in recent years because such violence is evident in the healthcare sector. The prevalence and consequences of victimization among healthcare professionals have been well-investigated but not in volunteers who have direct and prolonged contact with patients and visitors. The aim of this study was to investigate the prevalence of physical and psychological workplace violence, the psychological and emotional consequences for hospital staff and volunteers, and the coping strategies that they adopted. In the current study, both of these groups worked with patients suffering from chronic diseases in a hospital in northern Italy. The participants included 108 hospital staff and 96 volunteers in cardiology and oncology units. The results revealed that for the staff victims of physical or psychological violence, the increase in depressive and anxiety symptoms (both state and trait) corresponded to a greater use of coping strategies to avoid facing the event. For the volunteer victims of physical violence, an increase in state anxiety was associated with an attempt to cope with the discharge of emotion, whereas trait anxiety was associated with a coping strategy that represents a positive interpretation of life events. A worrisome finding was the number of staff and volunteer victims of physical and psychological violence who did not report these occurrences: only one third of staff and volunteers reported these events to management or to the police.